2022
DOI: 10.1155/2022/8182958
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Acupuncture in the Treatment of Neurodermatitis: A Systematic Review and Meta-Analysis

Abstract: Background. Neurodermatitis is a common chronic inflammatory skin disease associated with neurological dysfunction. This study aimed to explore the efficacy and safety of acupuncture and moxibustion in the treatment of neurodermatitis through meta-analysis. Methods. We comprehensively searched 9 databases, including PubMed, Cochrane Library, EMBASE, Web of Science, Scopus, China National Knowledge Infrastructure (CNKI), Wanfang Database, China Science and Technology Journal Database (VIP), and China Biomedicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Whether the neurodermatitis is a first episode or a recurrent state, the pathogenesis of itch is believed to involve dysfunctional inhibition and excitation of the cerebral cortex. Acupuncture may be beneficial for the regulation of the brain network centers involved in the transmission of messages mediating the symptom of itch, as well as the repair of nerve damage and regeneration of cells 5 ; acupuncture could theoretically affect pruritic symptoms in a variety of potential ways, such as reducing the production of pruritic mediators, inhibiting the number and function of local mast cells, activating k-opioid peptide receptors and class C fibers, promoting local skin repair by improving local blood circulation or metabolic capacity, promoting repair of nerve damage and/ or enhancing fibroblast regeneration.…”
Section: Commentmentioning
confidence: 99%
“…Whether the neurodermatitis is a first episode or a recurrent state, the pathogenesis of itch is believed to involve dysfunctional inhibition and excitation of the cerebral cortex. Acupuncture may be beneficial for the regulation of the brain network centers involved in the transmission of messages mediating the symptom of itch, as well as the repair of nerve damage and regeneration of cells 5 ; acupuncture could theoretically affect pruritic symptoms in a variety of potential ways, such as reducing the production of pruritic mediators, inhibiting the number and function of local mast cells, activating k-opioid peptide receptors and class C fibers, promoting local skin repair by improving local blood circulation or metabolic capacity, promoting repair of nerve damage and/ or enhancing fibroblast regeneration.…”
Section: Commentmentioning
confidence: 99%
“…The effectiveness of habit reversal is majorly based on the patients' neurodermatitis severity. In one case study, the patient (Sandra) with the mildest symptoms scratched around her ankle, about 3 inches up to her leg [9]. After 6 months of the habit reversal treatment, Sandra's neurodermatitis was completely healed.…”
Section: Effectiveness Of Habit Reversal Trainingmentioning
confidence: 99%
“…It reduces one of its most important and influential manifestations of neurodermatitis, itching. It is done by stimulating nerve fibers that will interfere with the transmission of itching [9]. Numerous studies found that acupuncture can help speed up metabolism, strengthen fiber cells, reduce local inflammation, and improve microcirculation.…”
Section: Effectiveness Of Traditional Chinese Medicinementioning
confidence: 99%